IMPLEMENTING OF ACTIVE TRAINING METHODS IN THE PROFESSIONAL TRAINING OF FUTURE PSYCHOLOGISTS BY THE WAY OF SOLVING LIFE SITUATIONS - Litvinenko, Irina (PSYCHOLOGICAL JOURNAL, 2017)
It is emphasized that the state educational policy of our country is aimed at improving of the quality of professional training of future specialists. This is especially true for the training of practicing psychologists who are in great demand on the great part of social practices. Today it is difficult to imagine any branch or field of activity that would not include the practicing psychologist as an active participant with his or her knowledge and technologies. This fact emphasizes once again that modern psychological science is becoming more and more practical-oriented, and therefore the requirements for a graduate student-psychologist are quite high. It is noted that a modern graduate of the faculty of psychology should do and act, and not only be able to talk about psychology, so that is to be an applied psychologist. It is emphasized that human life is impregnated with diverse life situations that affect its quality, the picture of the world, the model of human behavior, the degree of his or her world, the openness to other people and health. That is why one of the main tasks of a practicing psychologist is the psychological assistance to every person in solving life situations, regardless of his or her age, social status, etc., and these life situations are often psycho-traumatic, taking into account of the events that are taking place in our state. Deals with topical issues of training students of psychology, based on research results from leading scholars and teachers. Analyzed ways of effectiveness increase the study of psychology and prove feasibility of using active learning methods, among which an important place occupied by the situational. Give an algorithm the analysis of situations in life in the surrounding the process out educational, provides definitions of concepts such as “the situation”, “social situation”, “life situation of the individual” leading scientists, of domestic and foreign scholars in the framework general, age-related, social psychology. It is noted that the use of situational methods of instruction allow to generate psychology students readiness for independent professional activity, ability to solve life situations of varying complexity, develop tolerance, empathy, removed adult egocentrism. Also highlights some of the steps of vocational training outside the classroom (in the framework of the psychological circle “Psyche” a discussion club “At the crossroads of thoughts”), involving for the analysis, discussion of life situations specialists (lawyers, social workers, etc.).